The use of the reverse shock index to identify high-risk trauma patients in addition to the criteria for trauma team activation: a cross-sectional study based on a trauma registry system. Issue 6 (21st June 2016) - Kuo, Spencer C H; Kuo, Pao-Jen; Hsu, Shiun-Yuan; Rau, Cheng-Shyuan; Chen, Yi-Chun; Hsieh, Hsiao-Yun; Hsieh, Ching-Hua
Abstract : Objectives: The presentation of decrease blood pressure with tachycardia is usually an indicator of significant blood loss. In this study, we used the reverse shock index (RSI), a ratio of systolic blood pressure (SBP) to heart rate (HR), to evaluate the haemodynamic status of trauma patients. As an SBP lower than the HR (RSI<1) may indicate haemodynamic instability, the objective of this study was to assess whether RSI<1 can help to identify high-risk patients with potential shock and poor outcome, even though these patients do not yet meet the criteria for multidisciplinary trauma team activation (TTA). Design: Cross-sectional study. Setting: Taiwan. Participants: We retrospectively reviewed the data of 20 106 patients obtained from the trauma registry system of a level I trauma centre for trauma admissions from January 2009 through December 2014. Patients for whom a trauma team was not activated (regular patients) and who had RSI<1 were compared with regular patients with RSI≥1. The ORs of the associated conditions and injuries were calculated with 95% CIs. Main outcome measures: In-hospital mortality. Results: Among regular patients with RSI<1, significantly more patients had an Injury Severity Score (ISS) ≥25 (OR 2.4, 95% CI 1.58 to 3.62; p<0.001) and the mortality rate was also higher (2.1% vs 0.5%; OR 3.9, 95% CI 2.10 to 7.08; p<0.001) than in regular patients with RSI≥1. The intensive care unit length of stay was longer in regular patients with RSI<1 than in regular patients with RSI≥1. Conclusions: Among patients who did not reach the criteria for TTA, RSI<1 indicates a potentially worse outcome and a requirement for more attention and aggressive care in the emergency department.